Setting advertising objectives - Corkindale, David; Kennedy, Sherril (Cranfield School of Management, 1974)
The present report on the setting of advertising objectives is an integral part of the MCRU research activities. Although the broad aims of the research are to consider the methods of measuring advertising effectiveness, it was felt necessary to establish the benchmarks against which measurement is taking place - namely the advertising objectives. In consequence the report forms an intermediary stage of the overall research design, and is not an end in itself.